The Suinfort® Semen Supplement Counters Seasonal Infertility in Iberian Sows - Javier Piñán; Felipe Martinez-Pastor; Beatriz Alegre; Magdalena Maj; Roy N. Kirkwood; Juan Carlos Domínguez; Rodrigo Manjarín (Animals, 2021)
Suinfort®, a commercial semen supplement demonstrated to increase fertility and litter size in commercial sows, was tested to improve reproductive performance in Iberian sows. A total of 1430 Iberian sows were artificially inseminated (AI) with semen from Duroc boars and assigned by parity to receive the seminal additive Suinfort® containing 2 IU oxytocin, 5 µg lecirelin, and 2 mM caffeine (SF; n = 1713 AI), or to serve as non-supplemented controls (CON; n = 2625 AI). CON showed a lower fertility comparing to winter for spring (p = 0.001) and summer (p < 0.001); summer was lower than autumn (p = 0.012). SF removed this seasonal effect (p > 0.05). Fertility was significantly higher for SF sows during summer (p = 0.025) and autumn (p = 0.004). Total born, live-born, stillborn, and mummified piglets did not differ between CON and SF but were impacted by the season, with total and live-born decreasing in summer compared with autumn (p < 0.001) and winter (p = 0.005). In conclusion, seminal supplementation with Suinfort® improved the fertility of Iberian sows during periods of seasonal infertility.